Proteomic analysis of exosomes from Brucella abortus-infected macrophages reveals possible mechanisms of immune evasion and host modulation - Álvarez, Francisco; Arriagada, Vicente; Aburto, María Jesús; Ferrari, Ítalo; Alvarado, Ilse; Barrales, José; Vidal, Roberto; del Canto, Felipe; Gómez, Leonardo A.; Oñate, Ángel A. (Frontiers in Immunology, 2025)
IntroductionBrucella abortus is an intracellular pathogen that establishes chronic infections through immune evasion. Exosomes, a subtype of extracellular vesicles, mediate intercellular communication and can modulate host immune responses during infection. However, the proteomic composition and functional significance of exosomes from B. abortus-infected macrophages remain unclear.MethodsExosomes were isolated from RAW 264.7 macrophages infected or uninfected with B. abortus strain 2308, at 8 and 24 hours post-infection (hpi), using sequential centrifugation and immunoaffinity capture. Size and morphology were assessed by nanoparticle tracking analysis and transmission electron microscopy. Proteins were identified and quantified by label-free LC-MS/MS, followed by bioinformatic analyses for differential expression, functional enrichment, exclusive protein identification, and bacterial protein detection.ResultsExosomes from B. abortus-infected macrophages displayed distinct, time-dependent proteomic profiles. At 8 hpi, proteins involved in biosynthesis, energy metabolism, and endoplasmic reticulum processing were enriched, while lysosomal and antigen presentation components were reduced. At 24 hpi, enrichment shifted toward mitochondrial and redox regulation pathways, with sustained suppression of immune-related processes. Immune mediators (Csf3, Gsdmd, Ifi35) and retromer complex components were identified in a phase-specific manner. Sixty-six and twenty-four proteins were exclusive to infected exosomes at 8 and 24 hpi, respectively, reflecting a shift from metabolic/trafficking roles to immune regulation. Bacterial proteins GroEL and SodC were present at both time points, whereas Omp19, Omp2b, DnaK, and BAB1_0368 were restricted to early infection.ConclusionExosomes from B. abortus-infected macrophages exhibit dynamic proteomic remodeling that affects immune-related pathways, changes that may contribute to bacterial survival within the host. The presence of both host and bacterial-derived proteins within these vesicles suggests their potential relevance in brucellosis pathogenesis and highlights them as candidates worthy of further exploration as biomarkers or therapeutic targets.